Action research in production engineering: an exploratory study about its application in industry - Cerqueira Junior, Abinel Santiago; Caram, Fabio Santo; Arima, Carlos Hideo; Ribeiro, Rosinei Batista; Simões, Eliane Antônio (Brazilian Journal of Production Engineering, 2023)
Action research is a qualitative method that can be applied in production engineering to generate scientific knowledge and solve functional problems. This study aims to analyze the method and its application in production engineering in the industrial sector through exploratory research. For the development of the research, a literature review was conducted. Specialists with experience in the application of the method were consulted through a survey and interviews to identify the main methodological foundations of action research, its stages and techniques for its conduct in production engineering. The results achieved allow us to observe that the application of action research in the industrial sector covers several areas of concentration, such as digital transformation, industry 4.0 and operations management. The steps "plan action research" and "analyze data and plan actions" require greater time and effort to conduct the action research and, for due conduct of the method, the researcher must develop and create a relationship of trust with the participants who will be part of the research.
Keywords: Action Research; Production Engineering; Methodology; Productive Systems; Industry